Project Scheduling Optimization Using PERT and CPM Methods: Optimalisasi Penjadwalan Proyek Menggunakan Metode PERT dan CPM - Istighfarian, Muhammad ‘Athif; Mulyadi (Universitas Muhammadiyah Sidoarjo, 2025)
General Background Project scheduling is a critical aspect in ensuring timely completion and efficient resource allocation in construction and industrial projects. Specific Background Techniques such as Program Evaluation and Review Technique (PERT) and Critical Path Method (CPM) are widely applied to analyze project timelines and identify critical activities. Knowledge Gap However, limited integration of both methods in practical case studies leads to suboptimal scheduling decisions. Aims This study aims to analyze and optimize project scheduling using PERT and CPM to determine critical paths and estimated completion times. Results The analysis identifies key activities influencing project duration and reveals opportunities to reduce completion time compared to initial planning. Novelty The study provides a combined application of probabilistic and deterministic scheduling approaches within a single project context. Implications The findings support more structured planning and improved time control in project management practices Keywords: Project Scheduling, PERT Method, CPM Method, Critical Path, Time Pptimization Key Findings Highlights Critical activities determine overall project duration Probabilistic estimation provides flexible time prediction Combined approach yields more structured planning